2020
DOI: 10.3346/jkms.2020.35.e421
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Adverse Childhood Experiences (ACEs) and Stress among the Community-based Urban Pediatric Population in Korea

Abstract: Background: This study aimed to investigate the impact of exposure to adverse childhood experiences (ACEs) and stress among the community-based urban pediatric population in Korea. Methods: In 2017, the analysis was conducted on 3,937 children and adolescents in an urban area in Korea based on the impact of actual traumatic experience, addiction, and mental health. The respondents were excluded if they were missing data on the survey, resulting in a final sample size of 3,556. The collected data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…ACEs, such as childhood trauma, emotional or physical abuse, neglect, and social isolation, have negative effects on the developing brain, which reduce inhibition, memory and control, and studies have reported that certain internet use disorders, such as IGD, can occur ( Brand et al, 2016 ). A previous study showed that children and adolescent ACEs are highly correlated with stress ( Lee, Kim, & Bhang, 2020 ). Various studies have shown that traumatic histories are associated with problematic/addictive internet use ( Dalbudak, Evren, Aldemir, & Evren, 2014 ; Kaess et al, 2017 ; Kircaburun, Griffiths, & Billieux, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…ACEs, such as childhood trauma, emotional or physical abuse, neglect, and social isolation, have negative effects on the developing brain, which reduce inhibition, memory and control, and studies have reported that certain internet use disorders, such as IGD, can occur ( Brand et al, 2016 ). A previous study showed that children and adolescent ACEs are highly correlated with stress ( Lee, Kim, & Bhang, 2020 ). Various studies have shown that traumatic histories are associated with problematic/addictive internet use ( Dalbudak, Evren, Aldemir, & Evren, 2014 ; Kaess et al, 2017 ; Kircaburun, Griffiths, & Billieux, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of the 2017 report, results with significant scores for ACEs and numbers for which frequency of ACEs were not derived were reviewed. 35 36 As a result, in the process of composing the questionnaire in 2018, it was agreed to reduce the question numbers after discussion among researchers. The questions about family history of addiction were constructed and measured as standard questions of ACEs.…”
Section: Methodsmentioning
confidence: 99%